O102 We know about left gastric artery embolisation and will embio provide the next solution to treat obesity?. (22nd July 2022) - Patel, P; Thomas, R; Hamady, M; Hague, J; Raja, J; Tan, T; Bloom, S; Richards, T; Weiss, C; Prechtl, C; Smith, C; Thiagarajah, S; et al.
Abstract: Introduction: Left gastric artery embolisation (LGAE) is a minimally invasive procedure which has shown promising results for weight loss in recent studies and could play a key role as a treatment option in-between our current tier-3 and tier-4 services. Imperial College NHS Trust will sponsor the EMBIO trial, the first multi-centre double blinded randomised controlled trial comparing LGAE vs Placebo procedure to evaluate its efficacy on weight loss and obesity related comorbidities over a 12 month follow up period. Here, we perform a systematic review of the existing literature. Methods: 9 studies were reviewed. Studies which investigated weight loss as a % +- Ghrelin % change at 3, 6 and 12 months were included as these pre-defined time points correlate with the EMBIO protocol. 6 studies met our inclusion criteria, 5 single arm studies and 1 single blinded RCT. Results: N=62 patients were included in our analysis. Mean weight loss reported was 8.5%, 8.8% and 10% at 3, 6 and 12 months respectively post LGAE. Ghrelin levels reduced by 36%, 16.2% and 16.5% at 3, 6 and 12 months respectively post LGAE. To date, the only reported adverse events recorded include superficial gastric erosions healed on endoscopy by day 90 and one case of subclinical pancreatitis. Conclusion: LGAE potentially offers a day case procedure under local anaesthesia and sedation to treat obesity and its metabolic complications. The EMBIO trial will provide level 1 evidence to confirm if LGAE is a viable intervention for obesity and evaluate its safety profile. Take-home message: Left gastric artery embolisation could be the perfect solution to treat obesity in between existing tier-3 and tier-4 treatments.